Nilai Perjuangan Pebisnis Kopi Untuk Memperoleh Laba Pada Cerpen Filosofi Kopi Karya Dee Lestari - Anita Sari; Vani Dyah Novita; Eva Dwi Kurniawan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The purpose of this research is to describe the value of the struggle of two friends, namely Ben and Jody, in a literary work by Dee Lestari entitled the philosophy of coffee. This short story tells the story of Ben and Jody's successful struggle to make their dreams come true. The struggle makes two friends, Ben and Jody, ambitious in brewing coffee to gain profit and turnover. From this novel it can be seen that struggle and consistency can make someone achieve success. The method used is descriptive method. The source of this research uses data from the literary work used entitled Dee Lestari's Coffee Philosophy. The theory in this research is based on Joyomartono's theory, there are five types of struggle values, namely the values ​​of willingness to sacrifice, unity, respect, patience, and the spirit of never giving up, cooperation.